2016
DOI: 10.1016/j.apacoust.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sound level on perception of reproduced soundscapes

Abstract: a b s t r a c tThe aim of this work was to investigate the perception of soundscape reproduced by an ambisonic reproduction system on a horizontal plane, how the experience of space affected the perception of soundscape reproduction, and how the sound level adjustment on soundscape reproduction affected the perception of soundscape compared with actual conditions. There were three experiments conducted: a soundwalk in situ in Manchester (United Kingdom) city centre, listening tests in Salford (United Kingdom),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 7 publications
2
28
0
Order By: Relevance
“…Boren et al [28] captured the acoustic environment in different parts of New York with an ambisonic microphone. Davies et al [22] also used a FOA ambisonics microphone to record urban areas in Manchester, UK.…”
Section: Application Of Spatial Audio Recording In Soundscape Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Boren et al [28] captured the acoustic environment in different parts of New York with an ambisonic microphone. Davies et al [22] also used a FOA ambisonics microphone to record urban areas in Manchester, UK.…”
Section: Application Of Spatial Audio Recording In Soundscape Studiesmentioning
confidence: 99%
“…Perceptual accuracy is the basis of auralization [18], and is largely influenced by the spatial properties of sounds such as source distance, source location, and reverberation [19,20]. Several laboratory experiments on ecological validation of the reproduction systems have been conducted based on the psycholinguistic measure, such as semantic differential method [16,21,22]. Those studies compared the subjective responses of verbal descriptors on soundscape among in situ acoustic environments and the reproduced acoustic environments created by different techniques in laboratory conditions to explore the ecological validity of reproduction systems.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experiments can be carried out with acoustic environment recordings or a simulated acoustic environment. Experiments using acoustic environment reproduction have been validated [8] [13], but not the simulated acoustic environment. A method to validate an acoustic environment has been developed using semantic scales, which has been implemented for experiments in different conditions: in situ [13,14], in the laboratory using binaural reproduction [7,9], in the laboratory with a threedimensional ambisonic system [8,15], and in the laboratory with a two-dimensional ambisonic system [13].…”
Section: Introductionmentioning
confidence: 99%
“…Later, our previous study has shown that the dimension of Spatiality is not reliable [13]. The laboratory experiments were conducted using different reproduction systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation